Cabin Air Sampling Study Functionality Test. - Muir, Helen; Walton, Christopher; McKeown, Rebecca (Cranfield University; School of Engineering, 2008)
The Department for Transport (DFT), on behalf of the Government’s Aviation Health Working Group (AHWG), commissioned Cranfield University to organise, manage and deliver a functionality test of a variety of air sampling devices capable of detecting a wide range of compounds in a cabin air environment. The functionality test was to be the preliminary stage of a major monitoring study of the cabin air environment, which the Department intends to conduct.
Report prepared for the Department for Transport